O Telharmonium: arte e aparato para a geração e distribuição de música eletricamente - Braga, Rodrigo Trevisan (2016)
The Telharmonium was a musical instrument created in the late nineteenth century, of great technical complexity and size, coming to occupy a three-story building in New York City. Telephone cables were used to stream music for homes, restaurants, clubs and other places, through a subscription service. Fruit of labor of Thaddeus Cahill (1867-1934), an electrical engineer, the instrument enabled change in the timber as it was played, resemble thus an orchestra. Cahill presented several patent applications, reformulating them every time, for over twenty years, and in 1897 obtained the registration. For a number of reasons – many of them related to music streaming system to subscribers – the Telharmonium had to be turned off, leaving, however, a great legacy for the construction of electric musical instruments. This research aimed to recognize in the work of Cahill the theoretical basis of science that gave rise to it. Thus, approached the ideas of H. L. F. V. Helmholtz (1821- 1894), present in his book on acoustics, tuning and music theory titled On the Sensations of Tone as a Physiological Basis for the Theory of Music, as well as the patents filed by Cahill during the development of Telharmonium. These results indicated that the theories presented by Helmholtz were used as a basis for the development of such a musical instrument